107k views
0 votes
How do I solve for (2√5−√3)^2?

2 Answers

7 votes
The answer is 23-4√15
User Hayk Davtyan
by
5.2k points
1 vote

Answer:


23-4√(15)

Explanation:

So we want to simplify:


(2\sqrt5-\sqrt3)^2

Note that this is in the format:


(a-b)^2

And we know that this is the same as:


(a-b)^2=a^2-2ab+b^2

Let 2√5 be a and let √3 be b. Thus:


(2\sqrt5-\sqrt3)^2\\=(2\sqrt5)^2-2(2\sqrt5)(\sqrt3)+(\sqrt3)^2

Simplify:


=(4(5))-4(\sqrt5)(\sqrt3)+(3)\\=20-4√(15)+3\\=23-4√(15)

And this cannot be simplified any further.

User Enu
by
4.8k points